Roles of Cholecystokinin in the Nutritional Continuum. Physiology and Potential Therapeutics - Miller, Laurence J.; Harikumar, Kaleeckal G.; Wootten, Denise; Sexton, Patrick M. (Frontiers in Endocrinology, 2021)
Cholecystokinin is a gastrointestinal peptide hormone with important roles in metabolic physiology and the maintenance of normal nutritional status, as well as potential roles in the prevention and management of obesity; currently one of the dominant causes of direct or indirect morbidity and mortality. In this review, we discuss the roles of this hormone and its receptors in maintaining nutritional homeostasis, with a particular focus on appetite control. Targeting this action led to the development of full agonists of the type 1 cholecystokinin receptor that have so far failed in clinical trials for obesity. The possible reasons for clinical failure are discussed, along with alternative pharmacologic strategies to target this receptor for prevention and management of obesity, including development of biased agonists and allosteric modulators. Cellular cholesterol is a natural modulator of the type 1 cholecystokinin receptor, with elevated levels disrupting normal stimulus-activity coupling. The molecular basis for this is discussed, along with strategies to overcome this challenge with a corrective positive allosteric modulator. There remains substantial scope for development of drugs to target the type 1 cholecystokinin receptor with these new pharmacologic strategies and such drugs may provide new approaches for treatment of obesity.